Avoiding mode-monotony: How world-class cross-country skiers use exercise mode variations to manage daily load - Walther, J.; Kocbach, J.; Sandbakk, Ø. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Cross-country (XC) skiers usually compete and train in two different styles (skating and classical) with several sub-techniques included. Additionally, XC-skiers also apply cross training by including unspecific modes like running and cycling into their training. While a wealth of research has investigated annual training characteristics in world-class skiers, little is known about the load management during shorter training periods and especially the role of exercise modes in training load management is sparsely investigated. Therefore, the purpose of this study was to investigate the mode-monotony and day-by day application of different exercise modes by world-class cross-country skiers in the context of volume and intensity of endurance training.